Pemberatan Hukuman Terhadap Residivis (Studi Kasus Putusan Perkara Nomor 50/Pid.B/2018/PN.Tab) - Ni Made Wahyuni Paramitha; I Ketut Sukadana; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2021)
With existence of law expected by state Indonesia become peaceful state and can prevent the happening of crime. Its function criminal law arrange life of society to be can create orderliness of public. These time often met by various crime case conducted by recidivist, where the recidivist don’t discourage to penalization which he have against the punismentin prison previously. Research problems of this study are (1) How arrangement of law to recidivist according to positive law in Indonesia? ( 2) How base consideration of judge in breaking a recidivist? This research use approach of normatif that is with method approach of legislation, conceptual, and approach of case. Result indicate that: ( 1) Arrangement of law to recidivist according to Indonesian positive law is pursuant to section 486 Criminal code which enter in certain type of crimes, in section 486 Criminal code arrange about maximum crime from some criminal of which can added by 1/3 one-third because conducting repetition of or deed of recidive. ( 2) Base consideration of judge in breaking a recidivist that is in the balance punish Assembly Judge of Tabanan constitution its decision regarding have proven of validly and assure mistake of defendant of Section assertion 362 Criminal code have precisely and correctness. But regarding dropped crime penalization to defendant according to writer don’t in agreement with the decision because of existence of dimness of norm and also not yet fulfilled sense of justice and rule of law which where judge ought to add 1/3 one-third from maximum crime threat of fundamental because defendant a recidivist.